The Application of Impromptu Technique to Improve Speaking ability of Vocational Students of Bengkalis State Polytechnic - Aswandi, Aswandi; Gunawan, M. I. (Politeknik Negeri Bengkalis, 2024)
Based on issues identified in the classroom, students at the State Polytechnic of Bengkalis had difficulties inspeaking. They struggled to understand and identify key points in the oral texts, and also had a limited vocabulary. Toaddress these problems, the researcher decided to apply impromptu technique as a learning medium. The aim of the researchwas to determine to what extent the use of impromptu technique could improve students' speaking ability. This researchwas conducted over two cycles. Each cycle consisted of four meetings: three for teaching speaking and one for the posttest. The participants were 22 students from the English department. Several instruments were used for data collection,including (1) observation sheets for students, teachers, and teaching steps, (2) field notes, and (3) Speaking ability tests.The findings revealed that the use of impromptu technique could improve the students’ speaking ability. This was evidentfrom the improvement in their average scores on speaking ability. The average score of the students before using thistechnique was at 51, which increased to 60 at the end of the research. In conclusion, the implementation of impromptutechnique enhanced the students' speaking ability in the English department at the State Polytechnic of Bengkalis. It notonly improved their test scores but also increased their interest in speaking activities.